Wnt16 signaling in bone homeostasis and osteoarthristis - Ye, Xiaoping; Liu, Xianwen (Frontiers in Endocrinology, 2022)
Wnts are secreted cysteine-rich glycoproteins involved in joint development and skeletal homeostasis and has been implicated in the occurrence of osteoarthritis. Over the past decade, Wnt16, a member of the Wnt family, has received widespread attention for its strong association with bone mineral density, cortical bone thickness, bone strength, and osteoporotic fracture risk. In recent years, further studies have shed light on the role of Wnt16 a positive regulator of bone mass and protective regulator of osteoarthritis progression. Transduction mechanisms and crosstalk involving Wnt16 signaling have also been illustrated. More importantly, local Wnt16 treatment has been shown to ease osteoarthritis, inhibit bone resorption, and promote new bone formation in bone defect models. Thus, Wnt16 is now a potential therapeutic target for skeletal diseases and osteoarthritis. This paper reviews our current understanding of the mechanisms by which Wnt16 signaling regulates bone homeostasis and osteoarthritis.